Report of the Seminar/Workshop on Tax Policy Formulation and Tax Administration (CARICOM Secretariat GeorgetownGY, 1987)
Records discussion and recommendations of two workgroups the first of which discussed the integration of tax policy and tax administration and effects of taxes on social and economic integration. Group two focused on the topics of tax compliance and evasion; manpower planning and production control; information systems and legal support for effective tax administration. Annexes contain full texts of speeches, lists participants and resource persons, and programme of activities.
IDS